Fatigue and neuromuscular function in long COVID: A one-year follow-up study - Isabella da Silva Almeida; Leandro Gomes de Jesus Ferreira; Marco Aurélio Vaz; Gerson Cipriano Junior; Monique Alves de Resende; Denis Cesar Leite Vieira; Rochelle Rocha Costa; Nicolas Babault; Rita de Cássia Marqueti; João Luiz Quagliotti Durigan (PLoS ONE, 2025)
Background Long COVID has emerged as a significant complication of SARS-CoV-2 infection. However, the long-term neuromuscular consequences of this condition, particularly one-year post-infection, remain poorly understood. This study aimed to determine the mechanisms of fatigue by comparing perceived fatigue, objective fatigability, functionality, muscle architecture, and electrical neuromuscular function in participants who had suffered severe or moderate COVID‑19 one-year post-infection with a healthy control group. Methods and Findings This longitudinal observational study followed participants for one-year. The assessments were conducted at the Laboratory of Muscle and Tendon Plasticity at the University of Brasília, Brazil. Participants who had suffered moderate or severe SARS-CoV-2 infection were compared to a control group. A baseline assessment was initially conducted (21–30 days post-symptoms onset or post-hospital discharge), followed by second (31–90), third (91–180), and fourth (181–360) assessments. Perceived fatigue, objective fatigability, functionality, muscle architecture, and electrical neuromuscular function were analyzed. The study included 30 controls (46.53 [42.10–51.43] years; 13 men [43.33%]), 22 moderate cases (38.27 [33.96–43.13] years; 10 men [45.45%]), and 18 severe cases (50.83 [45.19–57.18] years; eight men [44.44%]). Severe participants exhibited higher perceived fatigue in all assessments than the control group and at baseline and in assessment 4 compared to moderate cases, in addition to a lower torque and torque-time integral in all assessments of objective fatigability analysis compared to the other groups. The severe group also demonstrated reduced functionality, impaired muscle architecture (characterized by increased echogenicity), and higher chronaxie values in the electrical neuromuscular function assessment. Participants with moderate COVID‑19 exhibited alterations in perceived fatigue, reduced torque, and lower TTI, electrical neuromuscular function, and muscle architecture, particularly at baseline. Conclusions Severe participants continued to experience significant perceived fatigue even one-year post-infection, suggesting a slower recovery trajectory, that contributed to increased fatigability throughout the follow-up period. These results emphasize the role of musculoskeletal and neural mechanisms in post-COVID‑19 fatigue, highlighting the need for targeted, mechanism-based rehabilitation strategies. Trial registration NCT04961255